Prevalencia de Toxoplasmosis en gatos Domésticos (felis catus) en el Barrio La Laguna del Cantón Latacunga de la Carrera de Medicina Veterinaria de la Universidad Técnica de Cotopaxi en el período académico 2018 - Paredes Pacha, Byron Oswaldo (2018)
Toxoplasmosis is a disease caused by a microscopic protozoan parasite called Toxoplasma gondii. Many warm-blooded animals, including most pets, livestock, birds and people can get infected with T. gondii. Cats are the definitive hosts of T. gondii. It means that they are the only animals that transmit oocysts (the resistant state to the parasite environment) in their feces to infect other species of animals, including human beings. With this research work, we will determine the prevalence of toxoplasmosis in domestic cats in the Parroquia Ignacio Flores, La Laguna neighborhood, Latacunga, through the Indirect Elisa test. The number of cats that were chosen for the study was 50 and was chosen indistinctively, that is to say, by different ages, sex and breed. The venous route that was chosen for the required amount and greater access was the external jugular vein. Once the samples were sent and processed in the Agrocalidad Tumbaco Laboratory, interesting data on the prevalence of toxoplasmosis were obtained. From a total of 50 samples, we have 13 toxoplasmosis-positive cats which represent the 26% of the total sample. It is an important quantity because it is ¼ of the sample total. Then, 6 cats that are doubtful and represent the 12% of the total sample; it means that, for some time, they had the disease or had an active infection. Finally, we have 31 cats whose result was negative to toxoplasmosis and represent the 62% of the total sample. According to the statistics by age we have three groups: from 0-12 months, 1-5 years old and > of 5 years old. Cats from 0-12 months had a prevalence of 5 animals, which represents 10% of the sample. Cats from 1-5 year old had the highest prevalence of 8 animals, which represents 16% of the sample; while in cats older than 5 years, there was no prevalence. By sex, females have a higher prevalence with 10 positive females that represent the 20% of the sample; while in males, we have a prevalence of 3 positive animals that represents the 6% of the sample. By breeds, we have that in the La Laguna neighborhood, there are 3 breeds: mixed, Angora and Siamese. Mixed is the breed that predominates with a prevalence of 12 animals and represents the 24% of the sample; while in the Angora breed, we have the prevalence of 1 animal and represents the 2% of the sample. Finally, in the Siamese breed, there is no prevalence. These data indicate that in fact, there is toxoplasmosis in the cats from La Laguna neighborhood with a prevalence of 26%, which is an important public health disease because it is zoonotic. Once the cats were identified in the clinical record, it proceeded to talk to the owners to tell them everything related to this disease and then, provide the treatment to the animals.